Role of Laparoscopy in Evaluation of Various Blunt Abdominal Trauma (Medicine Today, 2024)
Introduction with Objective: The aim of the present study was to assess the role of laparoscopy in evaluation of various Blunt abdominal trauma (BTA) in tertiary care teaching hospital. Materials and Methods: A prospective observational study was conducted from 21st June 2016 to 21st December 2017 among 50 abdominal blunt trauma patients attending at Casualty Block, Dhaka Medical College Hospital, Dhaka, after obtaining requisite consent from the patients attendant. Data were collected through the assessment and investigation report of abdominal blunttrauma patients in the Casualty Department. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the role of laparoscopy in evaluation of various blunt abdominal trauma. Results: Most of the patients were from 21-30 years (36%) of age group followed by 11-20 years (32%). The median age of this study population is 27 years. Of the study population, 84% (n=42) were male and 16% (n=8) were female. Male-female ratio was 84:16. In this study, 62% (n=31) of patients underwent only laparoscopy and 38% of patients (n=19%) underwent laparoscopy followed by laparotomy. Perforation of gas containing hollow viscus (94.73%) is responsible for conversion of laparoscopy into laparotomy in patients with blunt abdominal trauma. Among 50 patients 14 patients (28%) developed post operative complications. Rate of wound infection was higher laparoscopy followed by laparotomy (n=11). One patient developed post operative collection following laparoscopy. The accuracy rate is 100% in laparoscopic evaluation of BTA in this study. Conclusion: laparoscopy is a useful modality for evaluating and managing hemodynamically stable blunt abdominal trauma patients.Medicine Today 2024, Vol.36 (2): 95-98